Diversity and Biomass of Macrophytes of Bahiara wetland Saran Bihar - Manoj Kumar Pandey, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Diversity and Biomass of Macrophytes of Bahiara wetland Saran Bihar